PARISIAN FLAN WITH RICE BRAN FLOUR AS A DESSERT - Minta Harsana, Afina Ulul Mizani (Prosiding Pendidikan Teknik Boga Busana, 2020)
Research objectives: (1) Knowing the composition and the right proportion ofproducts parisian Flan with substitute bran flour. (2) Knowing the community's acceptance of theproduct Parisian Flan by substituting bran flour. (3) Knowing the nutritional value information onproducts Parisian Flan with substitute bran flour. The research method used in this study is Research and Development (RnD) with a 4D development model (Design, define, develop, dissemination). The recipe used in making Parisian flan bran is a recipe belonging to Chef Cedric (Cinema Bakery). Bran flour used as a substitute in this product as much as 30%. This product received an assessment of 3,825 based on the form assessment at the 2019 Final Project Exhibition which means this product is very popular and acceptable to the wider community. The biggest nutrient content in ParisianFlan Branis carbohydrate as much as 32.50545%. This proves that bran flour can be processed into a food ingredient and contains a fairly high nutrient content. Keywords: Parisian Flan Bekatul, tepung bekatul